Blunt Craniofacial Trauma as a Manifestation of Excited Delirium Caused by New Psychoactive Substances. Issue 6 (10th October 2016) - Byard, Roger W.; Cox, Matthew; Stockham, Peter
Abstract: The body of a 19‐year‐old male was found apparently concealed underneath bushes with recent head and facial trauma, and multiple superficial abrasions. Subsequently, it was discovered that the decedent had been running into objects and buildings following the ingestion the evening before of what was thought to be lysergic acid diethylamide (LSD). Blood staining of a nearby wall close to where the body was lying was in keeping with the described behavior. Toxicology revealed 3, 4‐methylenedioxymethamphetamine (Ecstasy), in addition to two only recently available drugs 2‐(4‐bromo‐2, 5‐dimethoxyphenyl)‐N‐[(2‐methoxyphenyl)methyl]ethanamine, (25B‐NBOMe), and 1‐(3, 4‐methylenedioxyphenyl)‐2‐(1‐pyrrolidinyl)‐1‐butanone, (MDPBP). At autopsy, the skull was fractured with cerebral swelling, contusions, and subarachnoid hemorrhage. Death was due to blunt cranial trauma against a background of mixed drug toxicity. The case demonstrates a rare cause of death in a drug‐induced acute delirium, as well as highlighting two new designer street drugs that may result in significant aberrant behavior.